Recent Progress in Electrochemical Detection of Human Papillomavirus (HPV) via Graphene-Based Nanosensors. (25th May 2021) - Mousavi, Seyyed Mojtaba; Behbudi, Gity; Hashemi, Seyyed Alireza; Babapoor, Aziz; Chiang, Wei-Hung; Ramakrishna, Seeram; Rahman, Mohammed Muzibur; Lai, Chin Wei; Gholami, Ahmad; Omidifar, Navid; Yousefi, Khadije
Abstract : In the present study, applications of advanced nanomaterials such as graphene oxide (GO), reduced graphene oxide (rGO), and graphene quantum dots (GQDs) as leading and potential candidates toward treating the human papillomaviruses (HPVs) were investigated. In this matter, a comprehensive summary of the formation of GO, rGO, and GQDs will be reported in detail. Continuous efforts have been exerted to develop high-performance biosensors and electrochemical detection systems toward accurate detection of HPV using novel routes. This review paper showed that HPVs appeared in different types and species. These HPVs have many complications on humans, and thus, there are different ways that a person could be exposed to them. Meanwhile, several routes of transmitting the HPVs to human cells are discussed too. Indeed, sexually transmitted diseases could be easily infected by HPVs, although the human immune system can also be boosted to treat this dangerous virus effectively. Some of the HPVs such as HPV-16 and HPV-18 are so dangerous, and HPV DNA could be detected in several vertical cancers. Herein, we reported and summarized some recent progress in electrochemical detection of HPVs using graphene-based nanosensors.